P1486 An unexpected case of paediatric heart failure. (17th January 2020) - Theocharis, P; Morrison, M L; Storring, N; Adhavaryu, K; Jivanji, S; Rosenthal, E; Miller, O; Mathur, S; Speggiorin, S
Abstract: A 9-month-old male presented in heart failure with a 2-day history vomiting that followed a viral upper respiratory tract infection 10 days previously. Echocardiography demonstrated a normally connected heart with a severely dilated and poorly functioning left ventricle with bright mitral valve papillary muscles. It was difficult to demonstrate the origin of the left coronary artery and retrograde flow was seen in the vessel (Fig 1, Panel A). The right coronary artery appeared normal. A gated cardiac CT was performed and showed a normal right coronary origin and no clear connection of the LCA to Ao and there was suspicion of retrograde filling. Images of the left coronary origin did not show clear connection of the LCA to Ao (Fig 1, Panel B). As the case was extremely unusual coronary angiography was performed which confirmed the suspicion of a dominant right coronary system with collateral connection to the left coronary system and retrograde filling and no antegrade filling of the LCA from the Ao (Fig 1, Panel C). This was consistent with atresia of the left coronary ostium, which was confirmed at operation. The left coronary sinus was opened, as was the roof of the left coronary artery and an anastomosis was performed to aorta using an autologous patch. The post operative TOE showed good flow into the LCA (Fig 1, Panel D). There was good and quick post op clinical recovery but the left ventricular function remains still poor at the moment with slow recovery as expected. The cardiac function will be monitored echocardiographically and the reconstructed coronary artery with CT.